Arabic as an Epistemological Foundation of Islamic Education and Qur’anic Exegesis - Muhammad Fariq Heemal Attruk; Budi Satriadi; Nisak Ul Mujahidah (MAN 4 Kota Pekanbaru, 2026)
This article examines Arabic as an epistemological foundation of Islamic education and Qur’anic exegesis. Moving beyond instrumental and symbolic conceptions of language, it argues that Arabic functions as an epistemological medium through which Islamic knowledge is constructed, Qur’anic meaning is produced, and interpretive authority and validity are established. Employing a conceptual integrative literature review, the study synthesizes scholarship from Arabic linguistics, Qur’anic studies, and Islamic education to demonstrate that meaning, authority, and epistemic legitimacy are linguistically mediated through Arabic semantic, syntactic, rhetorical, and phonetic structures. The analysis further highlights the epistemic consequences of detaching Islamic education from Arabic linguistic competence. While translation and multilingual pedagogical practices broaden access to religious knowledge, they necessarily involve interpretive transformation rather than semantic equivalence, with implications for depth of understanding, interpretive plurality, and epistemic accountability. Drawing on illustrative insights from non-Arabophone Muslim societies, the article clarifies how linguistic mediation becomes particularly visible in multilingual educational and interpretive contexts. By reframing Arabic from an auxiliary component to an epistemological foundation, this study contributes to contemporary debates on language, interpretation, and education in Islamic studies and offers a conceptual framework for critically evaluating pedagogical and interpretive practices within an increasingly mediated religious landscape.